Analysis of hybrid viscous damper by real time hybrid simulations. (1st November 2016) - Brodersen, Mark Laier; Ou, Ge; Høgsberg, Jan; Dyke, Shirley
Highlights: RTHS with a fraction of the damper force measured in the physical substructure. Partial validation of novel hybrid damper consisting of actuator and passive damper. Hybrid damper can increase stroke over passive damper using integral force feedback. Hybrid damper can increase attainable damping using filtered integration. Non-viscous damper force can lead to a reduced increase in damping. Abstract: Results from real time hybrid simulations are compared to full numerical simulations for a hybrid viscous damper, composed of a viscous dashpot in series with an active actuator and a load cell. By controlling the actuator displacement via filtered integral force feedback the damping performance of the hybrid viscous damper is improved, while for pure integral force feedback the damper stroke is instead increased. In the real time hybrid simulations viscous damping is emulated by a bang-bang controlled Magneto-Rheological (MR) damper. The controller activates high-frequency modes and generates drift in the actuator displacement, and only a fraction of the measured damper force can therefore be used as input to the investigated integral force feedback in the real time hybrid simulations.